2017
DOI: 10.1007/s10926-017-9745-7
|View full text |Cite
|
Sign up to set email alerts
|

Socially Constructed Hierarchies of Impairments: The Case of Australian and Irish Workers’ Access to Compensation for Injuries

Abstract: We conclude that these "sanist" attitudes undermine equal access to compensation for workplace injury as prohibited by the United Nations Convention on the Rights of Persons with Disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…The term "hierarchy of impairments" is used to describe how perceptions of and attitudes toward disabled people often depend on the type of impairment they have and how it occurred (Hernandez, Keys, and Balcazar 2000;Deal 2003.) Whether an individual's impairment is viewed positively, negatively or as a neutral factor depends largely on cultural factors, so this will vary between countries, but there is a rich literature indicating that persons with cognitive impairments are typically judged as less deserving than those with physical or sensory impairments (for example, Thomas 2000;Harpur, Connolly, and Blanck 2017). This has deep roots in the way that disability has been culturally constructed, and with the function of that construction within culture (Snyder and Mitchell 2010).…”
Section: Resourcesmentioning
confidence: 99%
“…The term "hierarchy of impairments" is used to describe how perceptions of and attitudes toward disabled people often depend on the type of impairment they have and how it occurred (Hernandez, Keys, and Balcazar 2000;Deal 2003.) Whether an individual's impairment is viewed positively, negatively or as a neutral factor depends largely on cultural factors, so this will vary between countries, but there is a rich literature indicating that persons with cognitive impairments are typically judged as less deserving than those with physical or sensory impairments (for example, Thomas 2000;Harpur, Connolly, and Blanck 2017). This has deep roots in the way that disability has been culturally constructed, and with the function of that construction within culture (Snyder and Mitchell 2010).…”
Section: Resourcesmentioning
confidence: 99%
“…Looking first at stigma: while existing research draws on stigma to debate a hierarchy of those protected in law compared with those who are not (Solanke, ), our study sought to discover whether there is a hierarchy between impairments as suggested by Harpur et al (). Our analyses show that those with a physical impairment were less likely to have their disability status challenged and/or employers were less likely to claim lack of knowledge of the impairment compared with claimants with a mental impairment.…”
Section: Discussionmentioning
confidence: 99%
“…As well as a hierarchy between those who are afforded legal protection against discrimination, Harpur et al () argue that there are hierarchies of impairment within disability. In Britain, until 2005, mental and physical impairments were treated differently: a mental impairment had to be ‘clinically well recognised’ to receive protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That work tasks and schedules may be adjusted to individualized needs, without the need to disclose a disability, is of particular relevance to people with stigmatized disabilities. Research documents high levels of employment bias and discrimination facing such individuals, both historically and presently [ 5 , 46 , 47 ]. Gig work further enables people to avoid disclosing private, non-task-relevant medical histories that sometimes are considered in different types of traditional employment decisions, albeit in contravention of laws like the ADA [ 1 , 48 ].…”
Section: Gig Workers With Disabilitiesmentioning
confidence: 99%